1998
DOI: 10.1046/j.1467-2494.1998.171740.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving skin function with CM‐glucan, a biological response modifier from yeast

Abstract: Preparations from yeast have been used for a long time for cosmetic and pharmaceutical purposes. Studies have identified glucan from the cell wall of baker's yeast as an immunologically active agent. Glucan is a poly beta-( 1-3)-linked glucopyranose of high molecular weight and belongs to the class of compounds known as biological response modifiers. Glucan preparations are involved in the activation of the body's natural defence mechanisms and in the acceleration of the skin's wound healing processes. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…[18][19][20] In the case of curdlan, its carboxymethylated derivative has good water solubility as well as good bioactivity, and it has been added successfully to cosmetics due to its immunocompetence. 21 However, the physico-chemical properties of carboxymethylated curdlan have not been examined yet, as far as the authors are aware. This paper reports the comparison of curdlan and its carboxymethylated derivative by means of rheology, DSC, and AFM, and gives a possible interpretation for the change of the macromolecular structure after carboxymethylation.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In the case of curdlan, its carboxymethylated derivative has good water solubility as well as good bioactivity, and it has been added successfully to cosmetics due to its immunocompetence. 21 However, the physico-chemical properties of carboxymethylated curdlan have not been examined yet, as far as the authors are aware. This paper reports the comparison of curdlan and its carboxymethylated derivative by means of rheology, DSC, and AFM, and gives a possible interpretation for the change of the macromolecular structure after carboxymethylation.…”
Section: Introductionmentioning
confidence: 99%
“…It could be speculated that beta-1,3/1,6 glucans also have a direct effect on stripping of the skin and perhaps also on redness, scaling and thickening. Betaglucans have been shown to offer protection against skin damage by detergent challenge or UV-A irradiation in healthy volunteers (Zulli et al, 1998), to be effective in the treatment of partialthickness burns in children (Delatte et al, 2001) and to improve wound healing in a mouse model of type 2 diabetes (Berdal et al, 2007). It should be noted that the effects of betaglucans were seen after topical application rather than ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Zulli et al . () suggested that glucan from the cell wall of baker's yeast could be used as an active ingredient for cosmetic and pharmaceutical purposes. This experiment showed that carboxymethyl glucan (CM‐glucan) protected skin cells against the depletion of antioxidant molecules upon UV‐A irradiation.…”
Section: Anti‐uv Light Effectmentioning
confidence: 99%